2021
DOI: 10.21608/jappmu.2022.115718.1026
|View full text |Cite
|
Sign up to set email alerts
|

Does Dietary Yeast Extract Improve the Performance and Health of Quail Breeders Reared under High Stocking Density?

Abstract: This study was designed to study the effects of stocking density without or with yeast extracts supplementation on productive and reproductive performance, digestive enzymes, blood biochemical parameters, and antioxidant and immune measurements of quail breeders. A total number of 336 Japanese quail birds at 8 weeks old were used. Quails were randomly distributed into 6 groups and 4 replicates maintained / each group in a complete randomized design. The 1 st group contained 36 birds (24 females and 12 males) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(46 reference statements)
1
1
0
Order By: Relevance
“…In addition, Ratriyanto et al (2020) recommended that the best SD for Japanese quails is 45 birds per m 2 (222.2 cm 2 /bird), combined with ascorbic acid supplementation (250 mg/kg), when reared in a hot climate. In line with our results, Reda et al (2021) reported that egg number, egg weight and egg mass of Japanese quail hens were significantly decreased due to increasing SD from normal cage SD (36 quails/m 2 ) to high cage SD (60 quails/m 2 ). Similarly, Ahmed et al (2022) demonstrated that as cage SD increased (from 252.20 to 106.73 cm 2 / bird) for Japanese quail hens their egg production rate, total egg mass and FCR were adversely affected.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, Ratriyanto et al (2020) recommended that the best SD for Japanese quails is 45 birds per m 2 (222.2 cm 2 /bird), combined with ascorbic acid supplementation (250 mg/kg), when reared in a hot climate. In line with our results, Reda et al (2021) reported that egg number, egg weight and egg mass of Japanese quail hens were significantly decreased due to increasing SD from normal cage SD (36 quails/m 2 ) to high cage SD (60 quails/m 2 ). Similarly, Ahmed et al (2022) demonstrated that as cage SD increased (from 252.20 to 106.73 cm 2 / bird) for Japanese quail hens their egg production rate, total egg mass and FCR were adversely affected.…”
Section: Resultssupporting
confidence: 92%
“…Several managerial and nutritional strategies can be adopted to minimize the negative effects of high SD on the welfare and performance of poultry. Some of these strategies have been reported including dietary supplementation with vitamin E (Selvam et al, 2017), yeast extract (Reda et al, 2021), organic acids (Dai et al, 2022), probiotics, prebiotics, synbiotics, plant-derived products, vitamins, and fatty acids (Sugiharto, 2022) and increasing the ND of the diet (DePersio et al, 2015;Khatibi et al, 2021;Gül et al, 2022). Therefore, the present study was designed to evaluate the response of laying Japanese quail stocked at three cage densities to feeding highnutrient-density diets.…”
Section: Introductionmentioning
confidence: 99%